Penggunaan Sumber Belajar Dalam Pengajaran Matematika - Eflin Nainggolan (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This research shows that the use of diverse learning resources in mathematics teaching improves student understanding. Textbooks, visual materials, math apps and math manipulatives help students with different learning styles. Internet-based and diverse learning resources also increase students' interest in mathematics and relate it to everyday life. The literature review method was used to reorganize, analyze, and synthesize existing literature rather than to collect primary data through experiments or surveys. These results emphasize the importance of mathematics teaching approaches that utilize diverse and intelligent learning resources. Teachers need to keep abreast of educational innovations and technologies to ensure effective and relevant mathematics education for students. This research provides a solid foundation for the improvement of mathematics teaching in schools and better understanding by students.